Seminar Kewirausahaan – Mengubah Hobi Menjadi Cuan PPGT Nonongan Salu - Olivia Devi Yulian P; Wilma Dian A; Lisa Kurniasari W; Mey Enggane L; Abedneigo C. Rambulangi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This activity aims to provide counseling about turning hobbies into profits at PPGT Klasis Nonongan Salu, which is one of the organizational/community activities within the intra-ecclesiastical management. This seminar was carried out with the aim of providing knowledge to teenagers that hobbies can be turned into profits. Apart from that, it provides insight and motivation to teenagers and prepares Christian young people to be independent and become agents of change for themselves, the congregregation and the nation. This activity was attended by around 30 people.